Distribution range and human-hippopotamus (Hippopotamus amphibious) conflict in the Lake Tana biosphere reserve, Ethiopia - Getasew Mulu; Dessalegn Ejigu (BMC Zoology)
Abstract Background Hippopotamus (Hippopotamus amphibious) is a semi-aquatic mammal that is considered the third largest living land mammal still alive on earth. The main objective of this study was to determine the distribution range and human-hippopotamus conflicts in the Lake Tana Biosphere Reserve, Ethiopia. Data were collected from June 2022 to January 2023. Total count methods were used to estimate the hippopotamus population, and Arc GIS was used to determine the distribution range and habitat suitability of hippopotamus. Structured questionnaire and focus group discussions were used to collect data on human-hippopotamus conflict. Data were analysed using One-way ANOVA, independent t-test, and chi-sqaure test. Results The mean population estimation of hippopotamus in in the study area showed 252.67 ± 15.9 with a density of 0.072 individuals per km2. The suitable slope analysis of hippopotamus along the the Lake Tana Biosphere Reserve’s shoreline revealed that 4.7% of the shoreline was most suitable, 48.4% moderately suitable, and 46.9% not suitable. Variations in the hippopotamus’ habitat suitability within the study area have been associated with a number of factors including availability of water, food, elevation, and vegetation cover. Crop raiding and overgrazing were the primary causes for conflict. Conclusion In order to conserve hippopotamus in the in the Lake Tana Biosphere Reserve, appropriate conservation measures including habitat protection and restoration, and community engagement and education need to be developed. Moreover, further research on the ecological aspects of the Lake’s ecosystem is required to ensure the conservation of hippopotamus.